Determinants of Welfare from an Islamic Perspective: Economic Growth, Income, and Employment on Welfare - Muhamad Agus Alfiyan Nur Ahmada; Siti Itsna Syamsiyah; Arifah Rohmatul Hidayah; Rokhmat Subagiyo; Muhammad Aswad (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to analyze the influence of economic growth, income, and employment on welfare in Indonesia in 2023. The research is motivated by the mismatch between increasing economic growth and equitable distribution of welfare, as well as inconsistencies in previous research findings regarding the effects of macroeconomic variables on welfare. A quantitative methodology is employed in this study, using secondary data obtained from the Central Bureau of Statistics (BPS). The population consists of 34 provinces in Indonesia in the 2023 period. Multiple linear regression is employed as the analytical method to evaluate the research hypotheses. The results show that simultaneously, economic growth, income, and employment have a positive and significant effect on welfare in Indonesia in 2023. Partially, economic growth has a negative and insignificant effect on welfare in Indonesia in 2023. Income has a positive but insignificant effect on welfare in Indonesia in 2023. On the other hand, employment has a positive and significant effect on welfare in Indonesia in 2023. These findings indicate that improvements in public welfare are more influenced by employment stability and productivity rather than economic growth and income, as the distribution of the latter is not necessarily equitable.